Efficacy of a Single Trapezoidal-Shaped 3-D Condylar Plate in the Osteosynthesis of Mandibular Condylar Fractures - Ashish Pillania; Yadavalli Guruprasad; Pooja Butoliya; Arti Butoliya; Khushbu Lamba Bhakar; Abhinay V. Deshmukh; Chandandeep Singh (Journal of Pharmacy and Bioallied Sciences)
Aim: In the osteosynthesis of mandibular condylar fractures, the goal had been to assess the stability of a single trapezoidal-shaped 3-D condylar plate. Materials and Methods: We evaluated 15 individuals who had mandibular condylar fractures. Under general anesthesia, the chosen patients underwent open reduction and fixation using three-dimensional titanium miniplates called trapezoidal condylar plates (TCPs). The Mini Retro Mandibular Approach and the Trans Masseteric Antero Parotid Approach were used to treat each of these fractures. Results and Conclusion: The three-dimensional Trapezoidal Condylar Plate titanium miniplates were found to be an efficient osteosynthesis device for stabilising condylar fracture and hence, yielded acceptable results in terms of achieving anatomical and functional stability.